2008
DOI: 10.1007/s00421-008-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fatigue-induced increase in relative work rate on temperature regulation during exercise

Abstract: Heat-loss responses during steady-load exercise are affected by an increase in relative work rate induced by muscle ischaemia or hypoxaemia. The present study investigated whether progressive increases in perception of exertion and relative oxygen uptake %VO2peak which occur during prolonged steady-load exercise as a result of progressively increased peripheral fatigue, might also affect the regulation of heat loss responses and hence the exercise-induced increase in mean body temperature. Ten male subjects fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rabita et al17 ) reported that the elements that improve jumping function are muscle tendon structure and intrinsic muscle hardness, although it is also important to take a neuromuscular function approach to training. This suggests that we were able to achieve increased foot hardness that was accompanied by an improved intrinsic foot flexor toe gripping strength and arch formation.…”
Section: Discussionmentioning
confidence: 99%
“…Rabita et al17 ) reported that the elements that improve jumping function are muscle tendon structure and intrinsic muscle hardness, although it is also important to take a neuromuscular function approach to training. This suggests that we were able to achieve increased foot hardness that was accompanied by an improved intrinsic foot flexor toe gripping strength and arch formation.…”
Section: Discussionmentioning
confidence: 99%
“…(37) By making our participants cycle at the same workload (pre-training 65%VO 2peak ) during both HSTs, they produced the same level of absolute oxygen consumption, translating into our design goal of a consistent rate of metabolic heat production pre-and post-training. It could certainly be argued that this approach would induce less cardiovascular strain on the participants during the post-training HST, since significant fitness improvements for both training groups were evident.…”
Section: P Revious Endurance Training Studies Have Demonstrated In-mentioning
confidence: 99%